Finding the Eye of the Octopus: the Limits of Regulating Outsourced Offender Probation in England and Wales - Mary Corcoran (Revue Française de Civilisation Britannique)
This article discusses the constraints on, and conflicts over, the oversight and regulation of mixed public-private entities, using the part-privatisation of the probation service in England and Wales – a policy called Transforming Rehabilitation (TR) – as its case study. The article shows how TR embodied a policy and set of practices that effectively undermined both institutional and political forms of scrutiny. Actions informed by neoliberal political dogma effectively strained regulatory systems, and short circuited the most important dimension of accountability in a liberal democracy – accountability of ministers to parliament. Ironically, although TR was subject to extensive regulatory scrutiny, the article concludes that these mechanisms were controverted by ministerial disregard for rules, procedures or the advice of civil servants, demonstrating that regulatory structures struggle to trump willfully pursued but ill-advised policy.